The role of engineering education for innovation in the 21st century. (7th May 2019) - Sunthonkanokpong, Wisuit; Murphy, Elizabeth
This conceptual paper first presents a synthesis of the central target and related concepts of five innovation policies from Asia. The paper then identifies how engineering education (EE) can help realise this target. Methods involved online, quantitative, key concept analysis combined with qualitative analysis of units of meaning. Analysis of the policies revealed that the overall target was social and economic prosperity. The prosperity is powered by a capacity for sustainability and inclusivity and by five other sub-categories of capacity as follows: human; relational; research and development; science, technology and innovation and; entrepreneurship and competitive. EE can contribute to social and economic prosperity by helping to build this capacity. Building capacity requires a shift from teaching as telling, to teaching as doing, from transmission of knowledge, to construction of knowledge, from teacher- to learner-centred learning and from didactic teaching to project- and problem-based learning situated in authentic, scientific, social and technological contexts.